The Social Media : How to Apply for Breastfeeding Promotion - Saengploy, Thitiporn; Chomphunit, Paphadar; Fhunpayom, Sillapachai; Sitthiboonma, Nalinee (NU Journal of Nursing and Health Sciences, 2021)
Breastfeeding has good effects on baby’s health such as reducing mortality, the occurrence of obesity, chronic disease, and infectious diseases. It also satisfies the basic needs of the baby. Breastfeeding is also beneficial to the mother. It reduces the chance of postpartum hemorrhage, breast cancer and endometrial cancer. (World Health Organization, 2017). World Health Organization recommended that the baby should be exclusively breastfed 6 months. After that, the breastmilk was given together with food by age until the age of 2 years or more. The survey results for exclusive breastfeeding rate in Thailand is still low. In 2019, only 14 percent of infants under the age of 6 months were receiving only breast milk. (National Statistical Office, 2020) Although many hospitals are promoted as a baby-friendly hospital initiative and work on the ten steps to successful breastfeeding policy. Nurses play a critical role to promote successful breastfeeding. Nowadays, social media has played a huge role in people's daily lives. The application of social media to promote breastfeeding is an attractive. So the authors analyzed the application of social media to promote breastfeeding based on the Social Support theory (House, 1981) to find an effective way to promote continued and effective breastfeeding.